Immune cell phenotype and function patterns across the life course in individuals from rural Uganda - Nalwoga, Angela; Nakibuule, Marjorie; Roshan, Romin; Kwizera Mbonye, Moses; Miley, Wendell; Whitby, Denise; Newton, Robert; Rochford, Rosemary; Cose, Stephen (Frontiers in Immunology, 2024)
Background To determine the pattern of immune cell subsets across the life span in rural sub-Saharan Africa (SSA), and to set a reference standard for cell subsets amongst Africans, we characterised the major immune cell subsets in peripheral blood including T cells, B cells, monocytes, NK cells, neutrophils and eosinophils, in individuals aged 3 to 89 years from Uganda. Methods Immune phenotypes were measured using both conventional flow cytometry in 72 individuals, and full spectrum flow cytometry in 80 individuals. Epstein-Barr virus (EBV) IFN-γ T cell responses were quantified in 332 individuals using an ELISpot assay. Full blood counts of all study participants were also obtained. Results The percentages of central memory (TCM) and senescent CD4+ and CD8+ T cell subsets, effector memory (TEM) CD8+ T cells and neutrophils increased with increasing age. On the other hand, the percentages of naïve T (TN) and B (BN) cells, atypical B cells (BA), total lymphocytes, eosinophils and basophils decreased with increasing age. There was no change in CD4+ or CD8+ T effector memory RA (TEMRA) cells, exhausted T cells, NK cells and monocytes with age. Higher eosinophil and basophil percentages were observed in males compared to females. T cell function as measured by IFN-γ responses to EBV increased with increasing age, peaking at 31-55 years. Conclusion The percentages of cell subsets differ between individuals from SSA compared to those elsewhere, perhaps reflecting a different antigenic milieu. These results serve as a reference for normal values in this population.